Vibrational, electronic and structural properties of 6-nitro- and 6-amino-2-trifluoromethylchromone: An experimental and theoretical study - Avendaño Jiménez, Leonor Patricia (2013)
Two 2-trifluoromethylchromones, 6-nitro-2-trifluoromethylchromone (1) and 6-amino-2-trifluoromethylchromone (2) were synthesized and characterized by NMR (1H, 13C and 19F), UV-Vis, vibrational (IR and Raman) spectroscopy, MS spectrometry, and compound (1) also by structural X-ray diffraction methods. This substance crystallizes in the monoclinic P21/c space group with Z=4 molecules per unit cell. In the solid, the fused rings and the amino group of (1) are coplanar and the trifluoromethyl group adopts a nearly staggered conformation. The NMR, vibrational and electronic spectra were discussed and assigned with the assistance of DFT calculations.